Regulations on Criminal Sanctions for Bribery in Corruption Cases - Muhammad Rustamaji; Shalih Mangara Sitompul; Wan Mohd Khairul Firdaus (Lembaga Contrarius Indonesia, 2025)
Corruption, particularly in the forms of bribery and extortion, remains a persistent problem within Indonesia’s social, political, and bureaucratic systems. Despite the existence of a comprehensive Anti-Corruption Law and related regulations, law enforcement authorities continue to encounter structural, substantive, and legal-cultural challenges in combating corruption effectively. This study aims to analyze the governance of criminal penalties in corruption cases, with a specific focus on extortion-related offenses. The research employs a normative legal method, utilizing legislative, comparative, and philosophical approaches to assess the coherence and effectiveness of existing legal norms. The findings demonstrate, first, that Articles 5, 6, and 12B of the Anti-Corruption Law contain overlapping legal elements, resulting in ambiguity in distinguishing between bribery and gratification and undermining the principles of legal certainty, clarity, and strict interpretation of criminal law. Second, the absence of clear normative boundaries has contributed to inconsistent law enforcement practices and unequal application of criminal sanctions. Third, a comparative analysis indicates that Malaysia has achieved greater regulatory coherence and institutional effectiveness through comprehensive legal reforms, particularly under the Malaysian Anti-Corruption Commission Act 2009, which aligns with international anti-corruption standards. This study concludes that legal reform in Indonesia should prioritize the harmonization of provisions on bribery and gratification, the clarification of corporate criminal liability, the strengthening of institutional independence, and enhanced inter-institutional coordination to achieve more effective, integrated, and targeted anti-corruption law enforcement.